Mathematical analysis of environmental system - Tanimoto, Jun (Tokyo : Springer, 2014)
This book is for all graduate students who are specializing in any environmental issue and who wish to grasp the fundamentals of physics that are required in various fields of science and engineering. The book provides the structural concept of the system state equation and its dynamics, which can be applicable to numerical solutions in several important areas such as heat and mass transfer and fluid dynamics. As a first step, there is a description of how to solve a linear system by conducting an analysis of temperature distribution in an infinite soil as a practical example. This exercise helps readers to fully understand what time and space discretizations are, and how actual numerical solutions should work. Because the concept of the system state equation relies on a vector?matrix form, the book shows how that particular form is applicable to other practical procedures: linear multi regression analysis, the least square method, and others. The book also gives the solution to non-linear dynamical systems and their applications. Although this book may appear to take an unusual approach, the author believes it will be inspiring and greatly helpful for the beginner who seeks a solid understanding of the basis of mathematics and physics for any environmental problems.
With bibliographical references and index.
Keywords: Environmental engineering -- Mathematical models